Van Der Waals gap-rich BiOCl atomic layers realizing efficient, pure-water CO2-to-CO photocatalysis - Yanbiao Shi; Jie Li; Chengliang Mao; Song Liu; Xiaobing Wang; Xiufan Liu; Shengxi Zhao; Xiao Liu; Yanqiang Huang; Lizhi Zhang (Nature Communications, 2021)
Efficient CO2 photoreduction in pure water remains challenging. Here, the authors propose to use van der Waals gaps-rich BiOCl atomic layers with low exciton binding energy and abundant surface oxygen vacancies for CO2 to CO conversion.